Polarization of intestinal tumour-associated macrophages regulates the development of schistosomal colorectal cancer - Wang, Zijian (J Cancer, 2021)
Tumour-associated macrophages (TAMs) can be divided into M1 and M2 TAMs. M2 TAMs play an important role in tumor progression, promoting a pro-angiogenic and immunosuppressive signal in the tumor. Previous studies have shown a correlation between schistosomiasis and colorectal cancer (CRC), but the specific mechanism has not been clarified. The differences between schistosomal CRC and non-schistosomal CRC were explored by analysing the clinicopathological data and survival time prognosis of schistosomal CRC and non-schistosomal CRC patients. The underlying mechanisms leading to the differences were investigated via tissue pathology experiments. Here, we investigated whether TAMs play a role in schistosomal CRC, leading to different clinicopathological features and prognoses in schistosomal CRC and non-schistosomal CRC patients and whether TAMs have a regulatory effect on the development and prognosis of schistosomal CRC. We found that schistosomal CRC and non-schistosomal CRC patients differ in age, sex, TNM staging and prognosis survival. Applying a logistic regression analysis model, the results showed that age, sex, pathological T stage and combined schistosomiasis were independent risk factors for CRC. Prognostic analysis of follow-up patients with schistosomal CRC found that the T stage, M stage and M2 TAMs numbers were independent prognostic factors for overall survival (OS). TAMs are significantly higher in tissues of schistosomal CRC than in non-schistosomal CRC patients, especially M2 TAMs. Studies on schistosomal colorectal tissue found that the expression of M2 TAMs increased with the malignant process of intestinal tissue. In summary, schistosomal CRC and non-schistosomal CRC patients have different clinicopathological features and prognosis, schistosomiasis is a risk factor for CRC and M2 TAMs are independent prognostic factors for OS.